Impact of Fire on Mechanical Properties of Slurry Infiltrated Fiber Concrete (SIFCON) - Anwar Saad Abbas; Mohammed Mansour Kadhum (Civil Engineering Journal, 2020)
This research aims to shed light on the fire flame effect on some mechanical properties of SIFCON samples, such as compressive strength, flexural strength and modulus of elasticity and comparing the results with CEN design curve and CEB. Higher temperature resistance is one of the most important parameters affecting the durability and service life of the material. This study comprised of casting and testing SIFCON specimens with 6% fiber volume before and after exposure to elevated temperatures. Two fire exposure duration of 1 and2 hours were investigate. In addition to room temperature, Silica fume was used as a partial replacement (10%) by weight of cement. It was found from the results achieved that after exposure to high temperatures, compressive strength, flexural strength and elastic modulus decreased. The drastically reduction of compressive strength took place with increasing temperature.  The residual compressive strength, flexural strength and elastic modulus at 1010 °C were in the range of (58.4 to 80.1%), (81.6 to 78.7%) and (30.4 to 32.8%) respectively. The compressive strength test results of this study together with results obtained by other investigators were compared with CEB strength-reduction curve and that of CEN. It was noticed that the test results agreed with CEN design curve rather than with that of CEB.